(untitled) (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2020)
The research was conducted with the aim to find out: (1) The influence of watching English movie by using subtitles toward students’ speaking skills for the first grade students of public senior high school 1 Jalancagak; (2) To know the response of student in learning process by using English movie with subtitles. This type of research is quasi-experiments research by using a quantitative method. Data collection is done by observation technique, test, and questionnaire. Data collected, then analyzed and drawn conclusions. The research was carried out in the odd semester in the academic year 2018/2019 at the first grade exactly X science 1. After conducting the pretest, the experimental class was given treatment in the form application of learning English for holiday plan material through watching English movies by using subtitles and held for four meetings. Research result shows that: (1) watching English movie by using subtitles can influence students’ speaking skills, students’ speaking skills from the aspect like as pronunciation, vocabulary, grammar, fluency, and comprehension further improved. This is addressed from the results of simple linear regression analysis, that significant value is 0.000 which means significant 0.000 < 0.05 so that H0 is rejected. Can also be seen from the results of student observation sheets there is an increase from one meeting to the next meeting; (2) based on the results of student questionnaire data processing it can be concluded that students provide positive responses to the method the researchers use in learning English is a method of watching English movie by using subtitles and giving a good response to the teacher (researcher).